2018
DOI: 10.1038/s41477-017-0098-1
|View full text |Cite
|
Sign up to set email alerts
|

Plant behaviour from human imprints and the cultivation of wild cereals in Holocene Sahara

Abstract: The human selection of food plants cannot always have been aimed exclusively at isolating the traits typical of domesticated species today. Each phase of global change must have obliged plants and humans to cope with and develop innovative adaptive strategies. Hundreds of thousands of wild cereal seeds from the Holocene 'green Sahara' tell a story of cultural trajectories and environmental instability revealing that a complex suite of weediness traits were preferred by both hunter-gatherers and pastoralists. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
71
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 55 publications
2
71
0
1
Order By: Relevance
“…Current crop phenotypes are the outcome of centuries of selection under agriculture, but also reflect the choices of early farmers among available wild plants (Mercuri et al, ; Preece et al, ; Sauer, ). Although crop evolution under domestication exerted a modest impact on root traits in our study, as discussed below, early farmers already showed a bias on root phenotypes of agricultural plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current crop phenotypes are the outcome of centuries of selection under agriculture, but also reflect the choices of early farmers among available wild plants (Mercuri et al, ; Preece et al, ; Sauer, ). Although crop evolution under domestication exerted a modest impact on root traits in our study, as discussed below, early farmers already showed a bias on root phenotypes of agricultural plants.…”
Section: Discussionmentioning
confidence: 99%
“…The significances (*p < 0.05; **p < 0.01) of domestication and functional group, as taken from Table 2, are displayed in the right corner of each graph availabilities and disturbance frequencies (Hawkes, 1983;Sauer, 1952;Zeven, 1973). Fast-growing and short-lived plants would become more abundant around settlements, would thrive better in early agricultural habitats and thus would respond better to the early attempts of cultivation and further domestication (Hawkes, 1983;Mercuri et al, 2018). Although rigorous comprehensive tests are still pending, wild progenitors tend to show specific leaf area and nitrogen content of leaves typical of fast-growing species, when compared with other wild herbaceous plants (Cunniff et al, 2014;Milla et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agriculture has given rise to uniform and predictable disturbed ecological niches (invasible habitats), which have proven highly beneficial for non-domesticated species or weeds (Boivin et al 2016;Bender et al 2016;Fuller and Stevens 2017), and some earthworm species. Blakemore (2009) has suggested that the origins of cosmopolitan (invasive) earthworms at family level are associated with domestication centers of plants and animals; that is, the presence of earthworms in crop fields is as old as agriculture itself (Blakemore 2009;Vigueira et al 2013;Mercuri et al 2018). The terms of the Millennium Ecosystem Assessment highlight the catalytic role of earthworms regarding two environmental services (Plaas et al 2019), namely the formation of soil and biogeochemical cycles, both of which are prerequisites for other environmental services (Brussaard et al 2012;Plaas et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to weeds (Willcox 2012;Vigueira et al 2013;Fuller and Stevens 2017;Mercuri et al 2018), it can be suggested that P. corethrurus and B. pearsei have shifted their preference from their natural habitat to agricultural environments, spreading geographically beyond their place of origin, and are currently key elements of agricultural environments. The presence of P. corethrurus and B. pearsei is associated with the development of pre-Columbian cultivation techniques in the Amazon (Clement et al 2015;Levis et al 2018;Boivin et al 2016;Watling et al 2018) and Maya (Ford and Nigh 2009;McNeil 2012;Boivin et al 2016) regions, respectively; for example, it is believed that P. corethrurus facilitated the formation of fertile soils in the Amazon area named "Terra Preta do Indo" (Glaser et al 2000;Ponge 2006).…”
mentioning
confidence: 99%